Accessing the Subconscious Quantum Computer Working With the Waves of our Aura (Spirit) NEMF for Health (Global Journal of Medical Research, 2023)
The article reveals the existence of a Quantum Computer in our Subconscious of which we are not consciously aware First hypnosis which put the Conscious to sleep to access the Subconscious revealed that hypnotized people with sleeping Conscious calculated at least 10 000 times faster This meant that in the Subconscious we have a computer more powerful than our conscious computer Farther studies revealed that the subconscious computer has unlimited possibilities to memorize and can predict events by jumps in the future or see past evens by jumps in the past Since only Quantum Computers allow quantum jumps to the future or the past it became obvious that in the Subconscious operates a powerful Quantum Supercomputer Since Quantum Computers operate with waves the waves of our aura Spirit field must be involved which I found to be nonlinear electromagnetic field NEMF
Keywords: quantum computer (QC); accessing the quantum computer; enlightenment is QC access